Variabel Cashless Dalam Memediasi Pengaruh Literasi Keuangan Terhadap Inklusi Keuangan Pada Usaha Mikro Kecil Dan Menengah (UMKM) Di Kabupaten Grobogan - Astohar Astohar; Dhian Andanarini Minar Savitri; Sari Rahmadhani; Sugiharti Sugiharti (Universitas Katolik Widya Karya Malang, 2023)
The public and entrepreneurs at this time (MSMEs) demand convenience in financial transactions. The public or business people do not need to carry cash for payments or transactions. This has an impact on efficiency and effectiveness for all parties which is the hope of the community itself. Cashless payments are now the demands of various parties for the smooth running of business and daily financial activities. Community financial literacy does not directly affect financial inclusion. The cashless variable is a variable capable of mediating the effect of financial literacy on financial inclusion. The population in this study were all SMEs in Grobogan Regency, Central Java. Collecting samples using accidental sampling technique. After going through the stages of compilation and screening, the samples that can be used are 147 samples. The analysis tool uses multiple multiple regression by carrying out other tests such as the normality test, the classical assumption deviation test, the goodness of fit test and the coefficient of determination test. For the intervening test using the sobel test with the SPSS program and www.danielsoper.com. The results of the study show that financial literacy has a significant positive effect on financial inclusion (H1 is proven) and also has an effect on cashless payments (H2 is proven). Cashless payment has a significant positive effect on financial inclusion (H3 is proven). Cashless payments are able to mediate the effect of financial literacy on financial inclusion in MSMEs in Grobogan Regency